Community empowerment in handling stunting through technology supporting food security and health - Endah Puji Astuti; Krisna Mutiara Wati; Muhammad Erwan Syah; Elvika Fit Ari Shanti; Tri Sunarsih; Pudji Astuti; Sarmin Sarmin; Andriyani Astuti; Claude Mona Airin (Universitas Muhammadiyah Magelang, 2024)
The prevalence of stunting in Indonesia, particularly in Gunung Kidul district, remains high at 23.5% in 2022. The Kosabangsa approach, integrated into the Village Development Plan (RPJM Desa) for 2020-2026, serves as a primary strategy for community empowerment, especially in agriculture and livestock. The methods employed include socialization, training, and mentoring, with a focus on functional food processing and home-based food processing. The results of this activity indicate an increase in the knowledge of PKK groups regarding infant and young child feeding practices and nutritional aspects, as well as a strengthening of their capacity to market local food products. This community service concludes that the integration of technology and a holistic approach to food security plays a crucial role in addressing stunting. Consequently, this community service not only focuses on short-term solutions to stunting but also aims to create a sustainable impact through community empowerment and overall food security enhancement.